Diversity of class 1 and 2 integrons detected in Escherichia coli isolates from diseased and apparently healthy dogs - Siqueira, Amanda K.; Michael, Geovana B.; Domingos, Daniela F.; Ferraz, Mirtis M.G.; Ribeiro, Márcio G. [UNESP]; Schwarz, Stefan; Leite, Domingos S. (Elsevier, 2016)
Escherichia coli is one of the major pathogens causing urinary tract infections (UTIs) and pyometra in dogs. The aims of this study were to investigate canine E. coli isolates for the presence of class 1 and 2 integrons by PCR/sequencing and to characterize these isolates and their integron-carrying plasmids. Isolates were characterized by phylotyping, XbaI-macrorestriction analysis and plasmid transfer experiments. Plasmids were analyzed by S1 nuclease-PFGE, replicon typing, conjugation and restriction analysis. Antimicrobial resistance was investigated by antimicrobial susceptibility testing and PCR/sequencing. From 158 E. coli of dogs suffering from UTIs (n = 51) and pyometra (n = 52) or being apparently healthy (n = 55), 13 isolates harboured class 1 (n = 10) or class 2 integrons (n = 3). They were distributed among the phylogenetic groups A (3/13), B1 (6/13), B2 (3/13) and D (1/13). Two isolates showed indistinguishable XbaI-patterns, but differed in the remaining characteristics. Another two isolates (UTI or apparently healthy) displayed different XbaI-patterns, but harboured similar plasmids. Integrons were found on plasmids of incompatibility groups IncF, IncF-IncFIC, IncFIB-IncHI2, IncFIB-IncN, IncFIC or IncHI2 and three of them were conjugative. Resistances to aminoglycosides, sulphonamides and trimethoprim were commonly detected. Class 1 integrons carried the gene cassette arrays dfrA12-orfF-aadA28, ΔdfrA17-aadA5, dfrA29, aadA7, aadA29 or dfrA12-orfF-aadA2-cmlA1-aadA1. Class 2 integrons carried the array dfrA1-sat2-aadA30. Two extended-spectrum β-lactamase genes (blaCTX-M-2) and one AmpC β-lactamase gene (blaCMY-2) were also detected on plasmids. These findings indicate the potential risk of the dissemination and persistence of E. coli and/or integron-carrying plasmids in companion animals.
Keywords: AmpC β-lactamases; Co-located resistance; Companion animals; Extended-spectrum β-lactamases; IS440-sul3